2018
DOI: 10.1038/s41598-018-26218-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of climate change in plant selection and millet domestication in North China

Abstract: While North China is one of the earliest independent centers for cereal domestication in the world, the earliest stages of the long process of agricultural origins remain unclear. While only millets were eventually domesticated in early sedentary societies there, recent archaeobotanical evidence reported here indicates that grasses from the Paniceae (including millets) and Triticeae tribes were exploited together by foraging groups from the Last Glacial Maximum to the mid-Holocene. Here we explore how and why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Climate change played a critical role in the selection of millet species for domestication during different periods in North China (Lu, 2017;Yang et al, 2018). However, geological records, including eolian deposits, lake sediments and soils, have shown that during the Yangshao Warm Period climatic conditions in Henan Province were much more favorable for cultivation than those seen today (Shakun et al, 2012;Marcott et al, 2013;Chen et al, 2015;Figures 4A,B).…”
Section: Discussion Foxtail Millet-broomcorn Millet Substitutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate change played a critical role in the selection of millet species for domestication during different periods in North China (Lu, 2017;Yang et al, 2018). However, geological records, including eolian deposits, lake sediments and soils, have shown that during the Yangshao Warm Period climatic conditions in Henan Province were much more favorable for cultivation than those seen today (Shakun et al, 2012;Marcott et al, 2013;Chen et al, 2015;Figures 4A,B).…”
Section: Discussion Foxtail Millet-broomcorn Millet Substitutionmentioning
confidence: 99%
“…Additionally, factors constraining or facilitating the development of the agricultural practices associated with these social transformations are complex, which have been proposed by scholars as climatic changes (Dong et al, 2012;Yang et al, 2018), social complexification (Wang J. H., 2005;Gao, 2009;Zhong et al, 2020), or developments in agricultural technology (Fan, 1988;Gao, 2009;Zhao, 2018). Climate change is supposed to have a greater impact on agriculture at large spatial scales, but geomorphologic condition will be more influential at smaller, more local scales (Robert et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two main domesticated C 4 crops, foxtail millet and common millet, were the staple foods in the semiarid regions of East Asia (Miller et al., 2016). Although the role of North China as the center of origin of millet agriculture has received widespread research attention (Barton et al., 2009; Cohen, 2011; Crawford, 2008; Lu et al., 2009; Yang et al., 2012), the factors driving the origin of millet cultivation are still debated (Cohen, 2011; Gignoux et al., 2011; Yang et al., 2018; Z. Zhao, 2011). Three types of hypotheses are commonly used to explain the rise of agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…One of the era-defining events in the Neolithic was the development of agriculture across the old world, followed by a substantial increase in the size of population and settlements [9][10][11][12]. Climate change has been considered to be a critical factor in the emergence and intensification of agriculture during the Neolithic period [13,14]. While the changes in temperature follow the same approximate trends in different regions of the Northern Hemisphere [15], precipitation shows distinct patterns affected by local climate (e.g., the arid central Asia and the Asian Monsoon Region) [16,17].…”
Section: Introductionmentioning
confidence: 99%